Corporate Governance and ESG (Environmental Social and Governance) Performance: Evidence From Chinese Listed Family Firms - Zhao, Yi-Wen (2022)
Corporate Social Responsibility (CSR) is now attracting a great deal of attention worldwide due to its consistency with sustainability. And ESG ratings and performance are one measure of companies' commitment and engagement with social responsibility. China, on the other hand, as an emerging economy, is relatively poorly equipped in terms of both awareness of CSR and ESG-related research. This research will focus on the ESG performance of Chinese family firms, which is a typical model of corporate governance with a long history and dominance in China. Based on Chinese listed family firms, this research investigates the relationship between corporate governance and corporate ESG performance by selecting 552 firm-year observations from 2018 to 2020. Through panel data analysis, this research reveals that family involvement at the senior executive level and the proportion of independent directors on the board are significantly and positively associated with corporate ESG performance. But surprisingly, the concentration of shareholding in family firms can negatively impact corporate ESG performance. In addition, the proportion of family members on the board and the outside chairman are not significantly correlated with corporate ESG performance. This research fills a research gap in explaining CSR in terms of two types of agency problems and attempts to provide practical implications for Chinese companies to improve their ESG performance.